Colonic Interposition between the Liver and Diaphragm: “The Chilaiditi Sign” - Nita Nair; Zeina Takieddine; Hassan Tariq (Canadian Journal of Gastroenterology and Hepatology)
A 90-year-old wheelchair bound male was brought to the emergency department with complaints of worsening abdominal pain over the last 2-3 days. The patient also had difficulty in passing urine. Abdominal examination revealed tenderness in the umbilical and hypogastric area without rebound tenderness or guarding. Computed tomography (CT) of the abdomen showed a loop of colon interpositioned between the liver and the right hemidiaphragm (the Chilaiditi sign), mimicking free air. Foley’s catheter was placed and the patient was managed conservatively. The patient clinically improved with improvement of the abdominal pain.